PERBANDINGAN TINDAK PIDANA PERKOSAAN ANTARA KUHP BARU INDONESIA DENGAN SEXUAL OFFENCES ACT 2003 INGGRIS - Tsuroyya, Chusnus; Nurtjahyo, Lidwina Inge (Faculty of Law, Universitas Pasundan, 2024)
Indonesian criminal law has undergone reforms since the promulgation of the Indonesia’s New Penal Code in 2023. This legal reform also refers to the provisions for the crime of rape which are regulated in Article 473 paragraph (1) of the Indonesia’s New Penal Code. This reform indicates that the paradigm regarding the rape crime in Indonesia has changed. With those changes, this research attempts to make a legal comparison between the New Penal Code and the England Sexual Offences Act 2003 – which is also a form of the legal reform. The research method used is normative juridical using analysis on legislation and comparative analysis. Based on a comparison on the regulation of the rape crime between the Indonesia’s New Penal Code and the England Sexual Offences Act 2003, there are several similarities and differences. Therefore, it could be seen the advantages and disadvantages of each regulation, both from the Indonesia’s New Criminal Code and the England’s Sexual Offences Act 2003. From this comparison, several advantages could be found in the Sexual Offences Act 2003 regarding the rape crime in England which could be an input on the regulation of the rape crime in the Indonesia’s New Criminal Code, so that better law would be created. Keywords: Rape, The New Indonesian Criminal Code, Sexual Offences Act 2003.